Subversion of complement by bacteria - Meri, Seppo (Henry Stewart Talks, 2017)
Innate immunity, Complement, Self/nonself discrimination, Borrelia escape from the immune system, Microbes that similarly inhibit the complement system, Vaccines based on microbial complement inhibitors